IMPLEMENTASI SISTEM AKUNTANSI UTAMA PADA PT. KABER AZEZE MEDIATEL (MADURA CHANNEL TV) SUMENEP - Firmansyah, Imam Darul; Widyastuti, Endang (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2018)
This research of writer conduct in April 2014, in PT Kaber Azeze Mediatel(Madura Channel TV) precisely JI. Adirasa No 5-7 Sumenep kolor. PT. KaberAzeze Mediatel (Madura Channel TV) is new company have peripateticoperational in Information area. that is Television Media. But that way institutethis can be told the including company which still young among other privatesector organization in Sub-Province of Sumenep. Target of this research tounderstand and description applying of Especial Accounting System exist in PT.KASER AZEZE MEDIATEL (MADURA CHANNEL TV) Sumenep. As for itsresearch type, descriptive research which have eksploratif or developmentalcharacter, its way same because obtained by data its same form, is different ofway to interpreting data and take of decision. In analysing data the researcher tobe use qualitative approach. In this technique data analyse the indication writerof Fundamental Elements Accounting System According for Mulyadi, that consistof: 1.Formulir 2. Journal 3. General Ledger 4. Ministrant Book. In anorganization very regrettably when organization, good that public and alsoprivate sector which have optimal human resource, still not yet can run systembetter specially Especial Accounting System, because a system represent efficacykeyword in moving forward an organization, good that in monetary pathmechanism and procedure which is resume in Especial Accounting System. Sothat as high as all competency had by Human Resource and progress oftechnology, without supported by a good system specially especial accountingsystem will become uselessly